RECURRENT PREGNANCY LOSS IN A PREGNANT WOMAN WITH SYSTEMIC LUPUS ERYTHEMATOSUS: A CASE REPORT AND LITERATURE REVIEW - Prima Della Fegita (Yayasan Nusantara Hasana Berdikari, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that predominantly affects women of reproductive age and poses significant risks during pregnancy. Pregnant women with SLE have a higher incidence of maternal and fetal complications, including recurrent pregnancy loss, preterm birth, and fetal growth restriction. Early recognition and multidisciplinary management are essential to improve pregnancy outcomes. We report a case of a 31-year-old pregnant woman (G4P0A3) at 19–20 weeks of gestation who presented with progressive joint pain, thrombocytopenia, alopecia, and photosensitive facial rash. The patient had a history of three previous pregnancy losses. Immunological examination revealed positive anti–double-stranded DNA antibodies, confirming the diagnosis of systemic lupus erythematosus with mild disease activity. Obstetric ultrasound showed a single live intrauterine fetus consistent with gestational age. The patient was managed collaboratively by obstetrics–gynecology and internal medicine teams. Treatment included systemic corticosteroids and hydroxychloroquine, along with supportive obstetric care. Despite conservative management, the patient developed signs of impending abortion and subsequently experienced a complete spontaneous abortion. Post-abortion care was provided, and the patient remained hemodynamically stable. This case highlights the significant impact of systemic lupus erythematosus on pregnancy outcomes, particularly recurrent pregnancy loss, even in patients with mild disease activity. Early diagnosis, preconception counseling, and close multidisciplinary monitoring throughout pregnancy are crucial to reduce maternal and fetal morbidity in women with SLE.